Clinical and pathological features of combined hepatocellular–cholangiocarcinoma compared with other liver cancers. Issue 6 (16th December 2018) - Wakizaka, Kazuki; Yokoo, Hideki; Kamiyama, Toshiya; Ohira, Masafumi; Kato, Koichi; Fujii, Yuki; Sugiyama, Ko; Okada, Naoki; Ohata, Takanori; Nagatsu, Akihisa; Shimada, Shingo; Orimo, Tatsuya; et al.
Abstract: Background and Aim: Combined hepatocellular–cholangiocarcinoma (CHC) is a primary liver cancer containing both hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) elements. Its reported clinicopathological features and prognoses have varied because of its low prevalence. This study aimed to clarify these aspects of CHC. Methods: We enrolled 28 patients with CHC, 1050 with HCC, and 100 with ICC and compared the clinicopathological characteristics and prognosis of CHC with HCC and ICC. We also analyzed prognostic factors, recurrence patterns, and management in CHC patients. Results: The incidences of hepatitis B virus and high α‐fetoprotein and protein induced by vitamin K absence or antagonists‐II levels were significantly higher among CHC compared with ICC patients. Multiple tumors were more frequent in CHC compared with the other groups, while vascular invasion and lymph node metastasis were more frequent in the CHC than the HCC group. The 5‐year overall survival and disease‐free survival rates for CHC were 25.1% and 22.6%, respectively. Overall survival was significantly lower than for HCC ( P < 0.001) but not ICC ( P = 0.152), while disease‐free survival was significantly lower than for HCC and ICC ( P = 0.008 and P = 0.005, respectively). Multivariate analysis identified carcinoembryonic antigen levels and tumor size as independent predictors in patients with CHC. Conclusions: The clinical features of CHC, including sex, hepatitis B virus infection, α‐fetoprotein, and protein induced by vitamin K absence or antagonists‐II levels, were similar to HCC, while its prognosis and pathological features, including vascular invasion and lymph node metastasis, were similar to ICC. Carcinoembryonic antigen levels and tumor size were independent prognostic factors in patients with CHC.